MENDISKUSIKAN HASIL PENGUJIAN HIPOTESIS PENELITIAN DALAM PENYUSUNAN DISERTASI : SEBUAH KAJIAN TEORITIS - I Gusti Ayu Agung Omika Dewi (KRISNA: Kumpulan Riset Akuntansi, 2021)
Discussing research results is an important stage in the dissertation preparation process. In general, in a dissertation there are several basic things that need to be considered in discussing research results, namely: summary of research results, interpretation of research results, placement of findings in the context of research, research implications, limitations of research, and suggestions for further research. One way to discuss research results is to look at whether or not the research hypothesis is supported. It is said that the ideal research is research whose hypothesis is supported or consistent with the theory and results of previous research. However, does the condition not supported by the research hypothesis indicate that a dissertation study has failed? This paper aims to discuss the process of discussing the results of dissertation research, especially on the results of hypothesis testing. After going through a theoretical study process, it can be seen that not supported by a hypothesis can actually enrich the research findings. If the hypothesis is not supported, of course, one must look for causes or reasons by discussing alternative explanations for the research findings and exploring what this means for philosophy, theory, and the world of practice in general.